RFID and XBee based automated verification of put-away operation for Warehouse Management Systems - (:unkn) unknown (IEEE Computer Society, 2016)
This study proposes a system using RFID and XBee technology to address and eliminate the problems resulting from human errors in put-away operations. The human errors in such operations are a serious problem that leads to a number of difficulties in production lines and supply-chain. The use of automated verification system in put-away operations in warehouses is rather rare. Therefore, the study draws from Information Technologies. Three modules - warehouse, racks, and forklifts - have been designed to ensure automated verification of error-free placement of goods. Also, a user interface is developed in Visual Studio C#.Net and SQL server is used for database management system. The developed system also provides monitoring of all steps of operation and enables real-time checking and supervision. Thus, it offers a reliable and transparent operation system, significantly contributes to effective management of supply chain and helps to improve high quality of fast and correct product delivery by minimizing the human errors. Thus, the study highlights the importance of automated verification system for an effective management of supply chain practices by establishing coordination among rack, forklift, warehouse modules, operator and product. © 2015 IEEE.
Keywords: Arduino; Put-away Errors; Put-away Operation; RFID; Warehouse Management; XBee Technologies